Is Overweight a Risk Factor for Adverse Events during Removal of Impacted Lower Third Molars? - Ricardo Wathson Feitosa de Carvalho; Belmiro Cavalcanti do Egito Vasconcelos (The Scientific World Journal)
Being overweight is recognised as a significant risk factor for several morbidities; however, the experience of the dentistry faculties focusing on this population is still low. The aim of the present study was to determine the occurrence of adverse events during removal of impacted lower third molars in overweight patients. A prospective cohort study was carried out involving overweight patients subjected to surgical removal of impacted lower third molar as part of a line of research on third molar surgery. Predictor variables indicative of the occurrence of adverse events during surgery were classified by their demographic, clinical, radiographic, and surgical aspects. Descriptive and bivariate statistics were computed. In total, 140 patients fulfilled the eligibility criteria, and 280 surgeries were performed. Patients’ mean age was 25.1 ± 2.2  years, and the proportion of women to men was 3 : 1. Eight different adverse events during surgery were recorded. These events occurred in approximately 29.3% of cases and were significantly associated with predictor variables (P < 0.05). Excess weight is recognised as a risk factor for the high rate of adverse events in impacted third molar surgery. The study suggests that overweight patients are highly likely to experience morbidities.